If I could turn back time [large type] - Harbison, Elizabeth M. (Center Point Large Print, 2015)
"Thirty-seven year old Ramie Phillips has led a very successful life, but lately Ramie has begun to feel discontented. On a boat with friends off the Florida coast, she dives off the diving board and suddenly finds herself back on the eve of her eighteenth birthday with a chance to live her life differently"--